Carbon management strategies – a quest for corporate competitiveness. (1st January 2013) - Busch, Timo; Schwarzkopf, Julia
This multiple case study analysis examines the extent to which five global car manufacturers apply carbon management strategies. Following a clear business strategy standpoint, the theoretical arguments are based on a framework developed by Orsato (2006). For this context, we highlight two key differences between carbon management and general environment strategies: the option of compensation and the demand for life-cycle efforts by stakeholders. Our analysis is based on eight carbon management strategies reflecting both carbon reduction and compensation strategies. The results show that the car manufacturers tend to embark on similar strategies in terms of carbon reductions, but less so for carbon compensation. Drawing on institutional theory, we explain this result by a lack of clearly established and widely expressed stakeholder expectations regarding carbon compensation. We conclude that carbon compensation may not yet be fully exploited and thus could be a short-term option when seeking competitive advantages in the automotive industry.